Leeonychiurus, a new genus from East Asia (Collembola: Onychiuridae: Onychiurini) - Sun, Xin; Arbea, Javier (Zootaxa, 2014)
A new genus of Onychiurini including five species is described from East Asia. Leeonychiurus gen. nov. differs in its antennal III sensory organ with granulated sensory clubs and 11 chaetae in the distal whorl of tibiotarsi. The main diagnostic characters of the genera from the tribe Onychiurini and the five species from the new genus are summarized. A new species, Leeonychiurus fusongensis sp. nov., is reported from northeast China and it can be easily distinguished from other species of the genus by the number of dorsal and ventral pseudocelli. The known Korean species L. polychaetosus is redescribed by the examination of the type materials.